"The used of intranet in disseminating information from top management to all staff : the case of Miri City Council (MCC)" / Josephine Jau - Jau, Josephine (2010)
E-Government was introduced for past decent years by Malaysia former Prime Minister Tun Dr Mohammad. The objective of the implementation of e-government is help to increase the productivity of our government servants especially in delivering their services to public. Introduction of intranet which is it will improve how the government operates internally. Thus this research will look how far the intranet have a correlation between the total usage of intranet and its effectiveness in disseminating the information for top management to all staffs which was conducted in Miri Sarawak called Miri City Council (MCC) by quantitative design to collecting data. Among the objectives that the researcher covered are (1) To study the usage of intranet towards MCC's effectiveness in disseminating information from top management to the staffs. (2) To know the relationship how frequent the usage of intranet with the effectiveness in disseminating the information.(3) To determine the main problems of the intranet usage amongst MCC's staff. Therefore, it is important for researcher to know how far the implementation e-government in stimulating their efficiency on intranet usage besides to accelerate the objectives of Vision 2020.